Extruded feed in different volume-concentrate ratios: in-vitro fermentation kinetics, consumption, and evaluation of lambs’ metabolic profile (Veterinária Notícias, 2020)
This study aimed both to evaluate the metabolic profile of lambsfed with extruded forage and concentrate containing different roughageconcentrate ratios (R:C) and to evaluate in-vitro ruminal fermentationkinetics of these rations. An experiment was carried out with 20 weanling,female crossbred lambs (½Dorper x ½Santa Inês) aged 120 ± 8 days. Thetreatments were four R:C ratios of extruded forage (Foragge®) and extrudedconcentrate (Beef Total®) – 30%F:70%C, 40%F:60%C, 50%F:50%C, and60%F:40%C – distributed randomly with five replicates. The analysistargeted energy metabolites (VLDL, triglycerides, and cholesterol), hepaticmetabolites (alkaline phosphatase, gamma glutamyltransferase [GGT], andaspartate aminotransferase [AST]), and protein metabolites (total protein,uric acid, urea, creatinine, albumin, and globulin). In-vitro gas productionwas quantified by inoculating the extruded rations in bovine ruminal fluidwith the following forage:concentrate proportions evaluated: 30%F:70%C,40%F:60%C, 50%F:50%C, 60%F:40%C and 70%F:30%C. Fermentationkinetic values were compared using parallelism test and curve identity atthe error probability level of 5%. A regression study was used to compare themeans of the metabolites at the error probability level of 5%. Average drymatter intake data are provided descriptively. The extruded rationincreased the hepatic metabolites (GGT and AST) without compromising theliver and kept the energy metabolites stable. Similarly, the serumconcentration of protein metabolites remained at normal levelsrecommended to the ovine species. In-vitro fermentation pattern displayedhigh gas production associated with high ration digestibility. The extrudedration provides protein and energy supply to meet the animals’ nutritionalrequirements without compromising their health.